Perbedaan Self-Efficacy Pencegahan Hipertensi Sebelum dan Sesudah Diberikan Edukasi Menggunakan Workbook pada Tenaga Kependidikan Kesehatan pada Salah Satu Perguruan Tinggi di Jawa Barat - Ristina Mirwanti; Melinda Ardian Dwi Cahya; Aan Nuraeni (Jurnal Keperawatan Muhammadiyah, 2022)
There are many health education methods, most of which do not involve the participants actively. Workbooks are educational media that encourage a person's active role and are expected to increase self-efficacy, where self-efficacy itself is a predictor of self-care management behavior. This study aimed to identify differences in hypertension prevention's self-efficacy before and after health education using a workbook. This study used a quasi-experimental method with a pre-post-test design with a control group. This study's population was teaching staff in two health faculties at one of the universities in West Java, Indonesia. The sample was determined using the convenience sampling technique and obtained 24 respondents divided into the control and intervention groups. Data collection using the instrument "self-efficacy for prevention of hypertension." The data were analyzed using the median and frequency distribution, while for the different tests, the Wilcoxon test and the Mann Whitney test were used. The median pre-test for self-efficacy was 105 and 110, while the post-test was 104.5 and 110.5 in the control and intervention groups. While the p-value of the difference test between the two groups before the intervention was 0.326 (p> 0.05), while after the intervention, the p-value was 0.002 (p <0.05). This study indicated a significant difference in the self-efficacy of hypertension prevention after being given education using a workbook in the two groups, where the self-efficacy score in the intervention group was higher than the control group. As a recommendation, workbooks can be used as an educational tool for hypertension prevention to increase self-efficacy.